Physical integrity and residual bio-efficacy of PBO-pyrethroid synergist-treated and pyrethroid-only LLINs after 1.5 years of field use in Western Kenya - Job Oyweri; Patrick O. Onyango; Maxwell G. Machani; Josephat Bungei; Yaw A. Afrane; Ming-Chieh Lee; Daibin Zhong; Guofa Zhou; Harrysone Atieli; John Githure; Guiyun Yan (PLoS ONE, 2025)
Background Long-lasting insecticidal nets (LLINs) are vital for malaria control in sub-Saharan Africa, but their durability is challenged by fabric decay and pyrethroid resistance. This study assessed the physical integrity and bioefficacy of piperonyl butoxide-LLINs (PBO-LLINs) and pyrethroid-only LLINs (pyrethroid-LLINs) after 1.5 years of use in western Kenya, where resistance is widespread. Methods A survey on net integrity and insecticide efficacy was conducted in randomly selected households (101–107 per group per visit) from three villages per net type group in Muhoroni Sub-County, Kisumu County. Physical integrity surveys were done after every six months while residual bio-efficacy was after every three months for 18 months. Physical integrity and residual bio-efficacy studies were conducted following WHO guidelines. Results PBO-LLINs exhibited higher physical integrity than pyrethroid-LLINs over time. At 18 months, 45.2% (61/135) of pyrethroid-LLINs and 21.8% (31/142) of PBO-LLINs were torn, with pHI values of 2494.1 ± 1696.4 and 1618.6 ± 1056.7, respectively. Net type, net age and house wall structures significantly influenced net integrity (p < 0.05). Torn nets were significantly more common in pyrethroid-LLIN households with mud-unplastered [OR=5.323 (95% CI = 1.685–16.816), p = 0.004] and corrugated iron walls [OR=6.31 (95% CI = 2.10–18.93), p < 0.001] and in PBO-LLIN households with mud-unplastered walls [OR=9.823 (95% CI = 1.487–64.898), p = 0.018]. Against the Kisumu susceptible Anopheles gambiae s.s, both net types decreased in mortality at baseline (when new) from 97.6% to 18.4% and 98.6% to 18.5% for pyrethroid and PBO-LLINs respectively at 18 months. Against a Bungoma pyrethroid-resistant Anopheles gambiae s.s, mosquito mortality with pyrethroid-LLINs declined from 36.9% when new to 6.8% at 18 months, while PBO-LLINs dropped from 55.6% to 11.8%. Conclusion Both physical integrity and bioefficacy of LLINs declined significantly within 18 months. The findings demonstrate that not all nets in the field offer maximum protection by this time point, calling for net care education and further evaluation of PBO-LLINs especially in pyrethroid-resistant regions.